2011
DOI: 10.1080/08997764.2011.573384
|View full text |Cite
|
Sign up to set email alerts
|

Market Size, Preference Externalities, and the Availability of Foreign Language Radio Programming in the United States

Abstract: Using data for 320 radio stations operating in the 50 largest Arbitron metro radio markets during 2004 that offered at least some programming in 1 or more of 19 different foreign languages, strongly positive statistical relations were found between the size of foreign language populations in the radio market and the amount, or variety, of radio programming in their respective language that is available. A preference externality effect was also found: consistently negative relations between the variety of forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…There was a significant audience for POC radio that was starkly separate from the largely white mainstream (Waldfogel, 2003). A 2011 media-economics study corroborated this: After analyzing 320 radio stations operating in the largest 50 radio markets in the U.S., researchers Xiaofei Wang and David Waterman concluded that there are indeed significant and positive correlations between the size of foreign language populations in the radio market and the number of radio programs available to POC in their respective languages (Wang & Waterman, 2011). On top of producing programming that could be "authentic," there was a clear economic advantage for Haitian radio stations to produce authentically Haitian programming.…”
mentioning
confidence: 94%
“…There was a significant audience for POC radio that was starkly separate from the largely white mainstream (Waldfogel, 2003). A 2011 media-economics study corroborated this: After analyzing 320 radio stations operating in the largest 50 radio markets in the U.S., researchers Xiaofei Wang and David Waterman concluded that there are indeed significant and positive correlations between the size of foreign language populations in the radio market and the number of radio programs available to POC in their respective languages (Wang & Waterman, 2011). On top of producing programming that could be "authentic," there was a clear economic advantage for Haitian radio stations to produce authentically Haitian programming.…”
mentioning
confidence: 94%